A Dendrite‐Structured RbX (X=Br, I) Interlayer for CsPbI2Br Perovskite Solar Cells with Over 15 % Stabilized Efficiency. Issue 20 (30th September 2020) - He, Jingjing; Ge, Bing; Hou, Yu; Yang, Shuang; Yang, Hua Gui
Abstract: Invited for this month′s cover is the group of Shuang Yang at the East China University of Science and Technology. The image shows a dendrite‐structured interlayer for CsPbI2 Br perovskite solar cells. The Full Paper itself is available at 10.1002/cssc.202001629 . Abstract : "Interface engineering is an important strategy for perovskite solar cells…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202001629 . View the Front Cover here: 10.1002/cssc.202002047 .